Virological failure in a pediatric cohort on a dolutegravir based regimen: a retrospective study in northwest Ethiopia, 2017–2023 - Zewdu, Woretaw Sisay; Zeleke, Mulugeta Molla; Ferede, Yared Andargie; Kassie, Achenef Bogale; Alemu, Muluken Adela; Moges, Tilaye Arega (Frontiers in Pediatrics, 2025)
IntroductionDespite the fact that antiretroviral therapy (ART) has reduced HIV/AIDS-related morbidity and mortality, pediatrics treatment failure remains a global concern. As a result, this study set out prudently to determine the prevalence of virologic failure and its predictors among children and adolescents on a Dolutegravir (DTG)-based antiretroviral regimen.MethodsA hospital-based retrospective cross-sectional study was conducted on children and adolescents on ART at Debre Tabor Comprehensive Specialized Hospital in Northwest Ethiopia from February-2017 to September-2023. Study participants were selected purposively. Data was collected using a semi-structured questionnaire and a data abstraction tool. Bivariate and multivariate logistic regression analyses were fitted to determine the linked factors. A p-value less than 0.05 was deemed to indicate a statistically significant association.ResultsAmong the 359 children and adolescents included in this study, 38 (10.58%) had developed virological failure. The odds of virological failure among children and adolescents were found to be increased by the age of the child <10 years (AOR = 4.41; 95% CI: 2.60–7.47), the care taker being a guardian or neighbor of patient (AOR = 2.03; 95% CI: 1.15–4.73), both parents passing away (AOR = 1.29; 95% CI: 0.12–2.68), CD4 counts ≤200 cells/µL (AOR = 4.3; 95% CI: 1.32–5.9), being infected with OIs (AOR = 2.03; 95% CI: 1.38–3.55), poor adherence status (AOR = 1.37: 95% CI: 1.12–3.11), adverse drug reaction (AOR = 1.75: 95% CI: 1.02–4.97), and anemic (AOR = 1.70: 95% CI: 1.03–5.15.04).ConclusionDespite potent DTG-based ARTs being introduced, virologic failure remains a concern in the study area. Special consideration should be directed towards children under the age of 10 years who are in the care of a guardian or neighbors, have lost both parents, are infected with opportunistic infections, have a poor adherence status, are experiencing adverse drug reactions, and anemic.